Cytotoxic Effect, Anti-Proliferative And Cell Death Mechanism Of Latex C-Serum And Sub-Fractions Using Cell-Based Assay - Lam, Kit Lay (2018)
Latex from Hevea brasiliensis, the natural rubber tree, has never been reported for folk medicinal use although highly regarded as an economic importance. Latex was thought to play a biological role in the plant defense system against microorganisms and insects. Due to scarce information available on the studies of its biological effects on mammalian system, cell viability assay using MTT, real-time PCR, cell cycle analysis and protein profiler analysis were used to evaluate the anticancer effects of and cell death pathway induced by whole C-serum (WC) and its fractions against the cancer-origin cell lines.